2011
DOI: 10.1007/s13142-010-0012-0
|View full text |Cite
|
Sign up to set email alerts
|

If we only knew what we know: principles for knowledge sharing across people, practices, and platforms

Abstract: The improvement of health outcomes for both individual patients and entire populations requires improvement in the array of structures that support decisions and activities by healthcare practitioners. Yet, many gaps remain in how even sophisticated healthcare organizations manage knowledge. Here we describe the value of a trans-institutional network for identifying and capturing how-to knowledge that contributes to improved outcomes. Organizing and sharing on-the-job experience would concentrate and organize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Facilitation equips staff with the skills and self-efficacy to act in resolving problems, by accessing and leveraging their potential or latent absorptive capacity at the unit level. Benefits may extend beyond the unit if intra- or inter-organizational sharing leads to adoption and productive adaptations by other units [ 72 ]. Proposition 1 : Facilitation is a social integration mechanism that leads to realizing (latent) absorptive capacity potential in health services organizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facilitation equips staff with the skills and self-efficacy to act in resolving problems, by accessing and leveraging their potential or latent absorptive capacity at the unit level. Benefits may extend beyond the unit if intra- or inter-organizational sharing leads to adoption and productive adaptations by other units [ 72 ]. Proposition 1 : Facilitation is a social integration mechanism that leads to realizing (latent) absorptive capacity potential in health services organizations.…”
Section: Discussionmentioning
confidence: 99%
“…This is thought to be the only type of learning that leads to sustained behavioural change in organizations [ 30 ]. Finally, adaptive knowledge generated through facilitation within a clinical micro-system might lead to widespread improvements in organizational process, if mechanisms are in place to disseminate knowledge intra-organizationally [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through the embodied learning experiences, teachers were able to see many facets of the innovation and built their own understanding of the characteristics of the innovation. Dearing et al (2011) suggested an ''exemplary demonstration'' in a convincing manner to influence adoption decisions and thus increase the likelihood of diffusion, and in our study the infusion and lesson observation served the purpose of demonstration, specifically, students' significant improvement in answering open-ended questions and their engagement, enthusiasm, and thinking like scientists in the classroom, were regarded as relative advantages of MSL. The curriculum design activity rendered them a sense of ownership of the innovation and let them see the compatibility; the understanding of the innovation highlight more on the pedagogy rather than the use of applications, as well as assurance of systemic supports got from Q & A sessions convinced them of the simplicity.…”
Section: Discussionmentioning
confidence: 80%
“…In much of the literature, teachers' learning community and network building were highlighted (Scribner et al 1999;Sun et al 2013). In the context of diffusion of innovation, Dearing et al (2011) proposed the idea of an ''implementation registry'' in the domain of healthcare, which was an online resource for practitioners within or across different institutions for sharing knowledge about solutions to challenges during dissemination, diffusion and implementation of an innovation. The idea of sharing success and challenges from practices would also benefit teachers when they are about to adopt an innovation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…These concessions also require a shift from the traditional paradigm of linear translation of a predesigned product (the intervention developed through RCTs) through centralized change agents, to a paradigm where innovations are malleable with input from researchers and the end adopters (clinicians and staff) who can make insightful real-time improvements [19,20]. Additionally, if knowledge sharing can be facilitated among implementing staff then lessons about best practices, reasons for failure, and solution-providing champions can further affect the process of organizational learning through additional improvement [21,22].…”
Section: Discussionmentioning
confidence: 99%